The Influence of e-Performance, Discipline, and Additional Employee Income on the Loyalty of Regional Inspectorate Employees of North Sulawesi Province - Sembel, Valdano; Dotulong, Lucky O.H.; Sumarauw, Jacky (International Journal of Information Technology and Education, 2023)
Employee loyalty is a key element in the success and sustainability of every organization, including government organizations such as the Regional Inspectorate of North Sulawesi Province. Data collection in this study involved employees at the Regional Social Service of North Sulawesi Province with a sample of 100 people from a population of 1 49 employees whereas Where sample only focused on the whole Number of Auditors and Supervisors maintenance Affairs Government. Study This aims to Analyze the influence of e-performance, discipline, and additional Income Employees (TPP) towards Loyalty Employee Inspectorate North Sulawesi Province Region. The results of this research are (1) e-performance has a positive and significant effect on the Loyalty of North Sulawesi Province Regional Inspectorate Employees (2) discipline has a positive and significant effect on the Loyalty of North Sulawesi Province Regional Inspectorate Employees (3) Additional Employee Income (TPP) has a positive effect and significant to the Loyalty of North Sulawesi Province Regional Inspectorate Employees (4) e-performance, discipline, and Additional Employee Income (TPP) together have a significant effect on the Loyalty of North Sulawesi Province Regional Inspectorate Employees.